Enhanced Energy Density for P-Doped Hierarchically Porous Carbon-Based Symmetric Supercapacitor with High Operation Potential in Aqueous H2SO4 Electrolyte - Xiaozhong Wu; Xinping Yang; Wei Feng; Xin Wang; Zhichao Miao; Pengfei Zhou; Jinping Zhao; Jin Zhou; Shuping Zhuo (Nanomaterials, 2021)
Phosphorus-doped hierarchically porous carbon (HPC) is prepared with the assistance of freeze-drying using colloid silica and phytic acid dipotassium salt as a hard template and phosphorus source, respectively. Intensive material characterizations show that the freeze-drying process can effectively promote the porosity of HPC. The specific surface area and P content for HPC can reach up to 892 m2 g−1 and 2.78 at%, respectively. Electrochemical measurements in aqueous KOH and H2SO4 electrolytes reveal that K+ of a smaller size can more easily penetrate the inner pores compared with SO42−, while the developed microporosity in HPC is conducive to the penetration of SO42−. Moreover, P-doping leads to a high operation potential of 1.5 V for an HPC-based symmetric supercapacitor, resulting in an enhanced energy density of 16.4 Wh kg−1. Our work provides a feasible strategy to prepare P-doped HPC with a low dosage of phosphorus source and a guide to construct a pore structure suitable for aqueous H2SO4 electrolyte.